Improving algebraic problem-solving achievement of secondary level students by using graph-based visualization of three models - Ali, Imdad; Das, Samiran (International Journal of Evaluation and Research in Education (IJERE), 2025)
The study aims to investigate the algebraic problem-solving achievement (PSA) of secondary school students. The study is conducted to improve students’ algebraic PSA by using the graphical visualization of three models, which are integrated to analyze certain factors that contribute to algebraic PSA. The first model is constructed to analyze students’ intrinsic and extrinsic motivation in the prediction of algebraic PSA. The second model is constructed to analyze with the help of cognitive and affective self-concept. Also, the third model is constructed to analyze with the help of four factors, such as cognitive and affective self-concept, and intrinsic and extrinsic motivation. In this study, a descriptive survey design is used, in which 400 ninth-grade students are involved in the Morigaon District of Assam, India. The results of regression analysis in the first model explain 29.8% variance of algebraic PSA, the second model demonstrated that 64.9% variance of algebraic and the third model has highest 66.1% variance of algebraic PSA can be accounted by the linear combination of the four independent variables. The findings of this study can be utilized by secondary education institutions to improve students’ mathematical achievement as a whole.